The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-07623-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of ammonium to a N limited arable soil enriches a succession of bacteria typically found in the rhizosphere

Abstract: Crop residue management and tillage are known to affect the soil bacterial community, but when and which bacterial groups are enriched by application of ammonium in soil under different agricultural practices from a semi-arid ecosystem is still poorly understood. Soil was sampled from a long-term agronomic experiment with conventional tilled beds and crop residue retention (CT treatment), permanent beds with crop residue burned (PBB treatment) or retained (PBC) left unfertilized or fertilized with 300 kg urea-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…A furrow irrigation system is used at the experimental site. The climate is arid with a mean annual temperature of 24.7°C, and an average rainfall of 384 mm ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A furrow irrigation system is used at the experimental site. The climate is arid with a mean annual temperature of 24.7°C, and an average rainfall of 384 mm ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…They combined two N fertilizer application rates, i.e., no fertilizer versus 300 kg urea-N ha −1 , and two tillage-residue management practices, i.e., tilled bed planting with residue incorporated and permanent beds with residue retained. Earlier research showed that retention of crop residue reduced N availability affecting C and N dynamics, grain quality, and the bacterial communities ( 12 14 ). The aim of this study was to investigate how two agricultural practices, i.e., tillage and N fertilizer application, affected the bacterial community structure and the microbial functionality in the rhizosphere, roots, and stem of irrigated maize plants cultivated in a Vertisol soil.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed the effects of various fertilizer managements on AOB, which reported that although organic and inorganic fertilizer amendments together increased the relative abundance of 16S rRNA gene copies, plant growth and developmental phase played a key role in the structural composition and relative abundance ( Tang et al, 2019 ; Hernández-Guzmán et al, 2022 ). In contrast, another study has reported that change in fertilizer regimes rather than plant growth stage played a central role in changing the relative abundance and structural composition of AOB communities ( Chen et al, 2014 ; He et al, 2021 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%